Pornography and the Erotic Phantasmagoria. - Rosen, David (Sexuality & Culture, 2023)
Susan Sontag, in her classic 1967 essay, "The Pornographic Imagination," argued: "Tamed as it may be, sexuality remains one of the demonic forces in human consciousness .... "In the last half-century, Sontag's demonic force of sexuality has transformed pornography and the "pornographic imagination"—let along social relations between women and men. In this essay, I adopt Walter Benjamin's concept of phantasmagoria—a magic-lantern show of optical illusions, rapidly changing size and blending into one another—as the metaphoric commodity form of postmodern capitalist society, fetishism-on-display. I examine the evolution of technological forms of pornographic representation over the last two centuries, including the magiclantern, daguerreotype, photography, stereoscope and film as well as the internet, erotic toys, electronic devises, VR and sex robots. These developments are set against a background of equally profound legal and cultural developments that have recast the sexuality of postmodern America. I argue that these (and other) developments have recast patriarchy and, in some important ways, the sexual relations between "consenting" adults. I conclude reflecting on the current intellectual and political debate about pornography between "pro-sex" and "anti-sex" feminists. With the enormous increase in the production and availability of pornography, I ask, perhaps "quantity" can give way to improved "quality"? I ask whether today's sexual phantasmagoria can fashion a "new" feminist sexuality—and a more humane pornography?